Analisis E-Service Quality Dalam Penggunaan Layanan Mobile Banking Menggunakan Metode Important Performance Analysis (IPA): Studi Kasus pada Nasabah Bank Kalbar Cabang Sa - Maiyora, Gusvionita; Mustikasari, Ati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Todays, the use of mobile banking has become more widespread, with most banks providing mobile banking services that are equipped with attractive features. People also switch from conventional transactions to mobile banking. Therefore, this study aims to measure user expectations for the quality of e-service services from the Mobile Bank Kalbar application and assess user satisfaction in using it. This research method involves quantitative analysis involving 100 respondents using Mobile Bank Kalbar. Data was collected through interviews, questionnaires, observation, and literature study. The results of the study show that the implementation of E-service Quality in mobile banking is quite good, although user expectations for the service are still low, so further improvements are needed in mobile banking services.